2020
DOI: 10.1111/tbed.13812
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Influenza D virus infection in European livestock as determined in serology studies: Are we underestimating its spread over the continent?

Abstract: Influenza D virus (IDV) is a novel orthomyxovirus that was first isolated in 2011 in the United States from a swine exhibiting influenza-like disease. To date, its detection is extended to all continents and in a broad host range: IDV is circulating in cattle, swine, feral swine, camelids, small ruminants and horses. Evidence also suggests a possible species jump to humans, underlining the issue of zoonotic potential. In Europe, serological investigations in cattle have partially allowed the understanding of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 52 publications
1
40
0
Order By: Relevance
“…Our data indicated a higher IDV seropositivity rate in cattle compared to the other animal species. These results are in line with data reported in European countries [ 8 ]. Indeed, cattle are considered as the main host for IDV, contributing to its spread.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our data indicated a higher IDV seropositivity rate in cattle compared to the other animal species. These results are in line with data reported in European countries [ 8 ]. Indeed, cattle are considered as the main host for IDV, contributing to its spread.…”
Section: Discussionsupporting
confidence: 93%
“…Seropositivity rates of IDV in domestic ruminants and swine and HI titers in Africa are much lower than those observed in other continents [8,14,19]. Antigenically different IDV strains were isolated in many regions of the world [5].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…is not yet completely elucidated, IDV seems to have a broad host range and has been described almost on all continents, suggesting an intercontinental transmission (Gaudino et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This paragraph highlights some discrepancies in the literature concerning the genetic diversity, immunity and clinical signs. So far, a couple of major circulating IDV lineages have been described in North America, Europe and Japan (Gaudino et al, 2020;Hayakawa et al, 2020;Murakami et al, 2016Murakami et al, , 2020 and reassortment events between these lineages were reported (Chiapponi et al 2019;Collin et al 2015). Furthermore, the haemagglutinin-esterase fusion (HEF) surface protein is antigenically stable suggesting that antibody escape mutants may not occur frequently (Wan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%